Composing Sound Structures with Rules. - Berg, Paul (Contemporary Music Review, 2009)
This article discusses the composition of musical structures, in particular sound structures, using generative systems based on work done at the Institute of Sonology in the 1970s. A view of the aesthetic background of G. M. Koenig is presented and used as a framework for the description of other software projects which often focused on micro-structure.